2015
DOI: 10.1186/s12992-015-0115-y
|View full text |Cite
|
Sign up to set email alerts
|

A study of mobile phone use among patients with noncommunicable diseases in La Paz, Bolivia: implications for mHealth research and development

Abstract: Background: While global momentum supporting mobile health (mHealth) research and development is increasing, it is imperative to assess the potential fit of mHealth programs in local settings. We describe the penetration of mobile technologies among Bolivian patients with noncommunicable diseases (NCDs) to inform research on mHealth interventions for the Andean region as well as low-and middle-income countries more generally. Methods: Five-hundred and fifty-nine NCD patients were identified from outpatient cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 35 publications
3
23
1
1
Order By: Relevance
“…Culturally safe text-based interventions for retention in a clinical trial were found to be effective with Maori participants by other researchers [ 34 ]. Similar results have been found in Indigenous communities near La Paz, Bolivia; most participants texted regularly and were open to mHealth interventions, provided Indigenous language preferences were taken into account [ 35 ]. Indigenous language use was mentioned as a key factor for successful distribution and uptake in 3 other studies [ 14 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 77%
“…Culturally safe text-based interventions for retention in a clinical trial were found to be effective with Maori participants by other researchers [ 34 ]. Similar results have been found in Indigenous communities near La Paz, Bolivia; most participants texted regularly and were open to mHealth interventions, provided Indigenous language preferences were taken into account [ 35 ]. Indigenous language use was mentioned as a key factor for successful distribution and uptake in 3 other studies [ 14 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 77%
“…SMS- or email-based programs offer several advantages over traditional mass media for health promotion and disease prevention, as they provide opportunities for interactive 2-way communication [ 15 ] and target specific, tailored behavior change communication [ 16 , 19 ]. Such interventions offer the opportunity for dissemination of automated, timely, and target-specific messages, which can be designed to complement or mirror in-person counselling [ 20 , 21 ]. For example, messages can offer tailored advice, behavior tracking, goal setting, encouragement, or personal feedback in different stages of behavior change [ 22 - 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cell phone penetrance in Bolivia is high. While no official numbers are available, a recent study in hospitals of the cities of La Paz and El Alto found that over 96% of patients ages 18-29 owned a cell phone [34]. Recent efforts from the Bolivian government have delivered cell phone service in rural areas of the country.…”
Section: Methodsmentioning
confidence: 99%